Tris(trimethylsilyl)silane and visible-light irradiation : a new metal- and additive-free photochemical process for the synthesis of indoles and oxindoles - Silva, Gustavo Piva da (2016)
A combined tris(trimethylsilyl)silane and visible-light-promoted intramolecular reductive cyclization protocol for the synthesis of indoles and oxindoles has been developed (Scheme 1).1 This straightforward and efficient protocol shows a broad functional-group tolerance and enables rapid and practical synthesis of functionalized nitrogen-based heterocycles in high/moderate yields under additive and metal-free, mild photochemical conditions. Besides the synthetic developments, the reaction mechanism was also investigated by a set of controlled experiments and UVvisible analyses, as well as kinetic study.2 From these studies, we have concluded that the reaction pathway for this strategy occurs through an Electron Donor-Acceptor (EDA) complex.3 to be continued ...